Near‐Infrared Light Triggered Soft Actuators in Aqueous Media Prepared from Shape‐Memory Polymer Composites. Issue 9 (10th June 2016) - Fang, Liang; Fang, Tianyu; Liu, Xiaoxia; Chen, Shunping; Lu, Chunhua; Xu, Zhongzi
Abstract : Soft actuators in aqueous media which work under the irradiation of near‐infrared light are prepared using composites of cross‐linked poly[ethylene‐ ran ‐(vinyl acetate)] and aniline black. Dual shape‐memory, temperature‐memory, and reversible shape‐memory effects of the composites in air and in water are all achieved. Releasing device and gripper are demonstrated to confirm the feasibility of the prepared composites to be used as soft underwater actuators. Abstract : Light triggered soft actuator in aqueous media has applications in operating underwater objects, creating liquid flow, and adjusting reaction velocity, etc. Here, composites prepared from commercial materials, poly[ethylene‐ ran ‐(vinyl acetate)] (EVA) and aniline black (AB), are reported as one cost efficient material for preparing such actuator, where EVA and AB work respectively as shape‐memory polymer matrix and near‐infrared light triggered photothermal filler. Upon irradiation, the temperature of the composites increases greatly with light power density and AB content. Light‐induced shape‐memory effect (SME) with recovery ratio >98%, temperature‐memory effect (TME), and reversible bidirectional shape‐memory effect (rbSME) of the prepared composites in air are realized. Higher light power density is required to trigger the shape recovery in aqueous media, while good SME, TME, and rbSME are also achieved. Releasing device and gripper are used to indicate the feasibility of the composites as light triggered soft underwater actuators.